Lagenorhynchus australis - James G. Mead; Robert L. Brownell, Jr. (Smithsonian Institution Press, 1993)
Lagenorhynchus australis (Peak, 1848). Mammalia in Repts. U.S. Expl. Surv., 8:33, pl. 6. TYPE LOCALITY: "South Atlantic Ocean, off the coast of Patagonia", Argentina, 1 days sail north of the Straits of LeMaire. DISTRIBUTION: Chile to Argentina: Valparaiso to Commodoro Rivadavia and Falkland Isis: Cold-temperate waters. One published (photograph) sighting in the tropical waters of the South Pacific, Cook Isis (Leatherwood et al. (1991). STATUS: CITES - Appendix II. SYNONYMS: amblodon, chilöensis. COMMENTS: Included in cruciger by Bierman and Slijper (1947) and Hershkovitz (1966a:67), but considered a distinct species by Fraser (1966), Rice (1977), Brownell (1974), and Mitchell (1975). Published as part of James G. Mead & Robert L. Brownell, Jr., 1993, Order Cetacea, pp. 349-364 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 353, DOI: 10.5281/zenodo.7352970